Improving Diagnostic Turnaround Time and Analytical Reliability in Clinical Biochemistry Laboratories: A Quality Management Framework (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Clinical biochemistry laboratories play a key role in diagnosis, triage, therapy monitoring and patient-flow decisions. Ongoing delays and inconsistent test reliability weaken their clinical value and cannot be corrected simply by increasing analyser speed. These problems often arise at poorly managed interfaces across the total testing process, including test requesting, patient identification, specimen collection and transport, accessioning, centrifugation, analysis, validation and result reporting.Objective: To create a comprehensive quality-management framework that shortens diagnostic turnaround time (TAT) while maintaining analytical reliability in clinical biochemistry laboratories.Methods: A narrative review was conducted using international laboratory quality standards, consensus guidance and peer-reviewed research on TAT, quality indicators, risk-based control, sigma metrics, autoverification and the total testing process.Findings: Sustainable improvement depends on defining TAT from the user perspective, decomposing it into measurable components, redesigning bottleneck-prone pre- and post-analytical steps, and applying analytical controls matched to method risk, clinical purpose and performance. In one published single-institution blood-gas implementation, rule-based autoverification reduced TAT from 27 to 18 minutes while the reported verification error rate fell from 2.0% to 0.05%, illustrating that speed and reliability can improve together when safeguards are validated and monitored. This review offers an integrated framework linking TAT metrics, risk controls and quality-management-system governance across the full testing cycle.Conclusion: A high-quality clinical biochemistry laboratory is not merely fast. It is a well-controlled socio-technical system that produces timely, traceable, clinically interpretable and analytically reliable results. Quality management provides the governance needed to improve speed and reliability simultaneously rather than trading one against the other.